Messianic mystics - Idel, Moshe, 1947- (New Haven : Yale University Press, 1998)
"One of the worl'ds leading scholars of Jewish thought examines the long tradition of Jewish messianism and mystical experience."
Pre-Kabbalistic Jewish forms of messianism -- Abraham Abulafia : ecstatic Kabbalah and spiritual messianism -- Concepts of messiah in the thirteenth and fourteenth centuries : theosophical forms of Kabbalah -- Messianism and Kabbalah, 1470-1540 -- From Italy to Safed and back, 1540-1640 -- Sabbateanism and mysticism -- Hasidism : mystical messianism and mystical redemption -- Concluding remarks.
Includes bibliographical references and index.
Print version record.
English.
JSTOR
Keywords: Messiah -- Judaism -- History of doctrines; Cabala -- History; Messie -- Judaïsme -- Histoire des doctrines; Kabbale -- Histoire; RELIGION -- Judaism -- Theology; Cabala; Messiah -- Judaism -- History of doctrines; History